Análise enunciativo-discursiva em comentários online na página de notícias da revista Veja da rede social Facebook - COSTA, Willian Gonçalves da (UNIFAP – Universidade Federal do Amapá, 2022)
The general objective of this work is to analyze the enunciative - discursive process in interaction comments in a news page of the VEJA Magazine of the social network facebook and, more specifically, we try to discuss, from concepts of polyphony and heteroglosia (BAKHTIN, 1998 [1934 -1935]) as does the process of interaction-discourse on this news page. We ground our study on the basis of discussions of discourse genres, concrete utterances, extraverbal context, and value appreciation (BAKHTIN, 2003 [1952/3], VOLOSCHINOV / BAKHTIN, 1926, PEREIRA, RODRIGUES, 2014, BRAIT, 2005). Considerations about treatments regarding discursive constructions in social networks, valid for work are as discussions of Santaella (2014) and Recuero (2010) regarding the networks. THE WORD-LOPES, 2006; FABRÍCIO, 2006), being carried out from the qualitative-interpretative approach of the type virtual ethnographic research (AMARAL et al., 2008), realized in the page of the VEJA Online magazine. The corpus delimited for this analysis is three news articles published on July 21, 24 and 27, 2017, between 05 to 12 comments referring to the posting of the main news, discussed based on the analysis criteria elaborated based on the native theoretical references research. The results of the analysis show that only the presence of conversational markers in the publications in comments is not sufficient for an understanding of the process of interaction and to make enunciative "want-to-say" of the interlocutors, which implies a return to the context and constitutive horizons and temporal) of the heteroglassical dialogical constructions, thus provoking the discursive present in a social environment. This has brought us a framework of responsive active understandings charged with ideological senses and volitional / evaluative discursive positions. Thus, we perceive the clash of opposing ideologies or ideas, identified in appreciative valuations that are not excluded, for they are intrinsically, immanently sociological.